HUBUNGAN POLA MAKAN DAN AKTIVITAS FISIK DENGAN KONTROL GLUKOSA DARAH PADA PENDERITA DM TIPE 2 DI RSUD CUT NYAK DHIEN MEULABOH - Anasril Anasril; Maryono Maryono; Tri Mulyono Herlambang; Ridha Fitri (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2024)
Diabetes mellitus sufferers have a high mortality rate and it is related to blood glucose control and lifestyle factors. Diabetes mellitus must be controlled routinely and sufferers must know the type of blood glucose control they have. Most sufferers' lifestyle factors include unbalanced diet and physical activity patterns. This study aims to determine the relationship between diet and physical activity with blood glucose control in type 2 DM sufferers at Cut Nyak Dhien Hospital, Meulaboh. This research is a type of quantitative descriptive research with a cross sectional design. The number of respondents was 68 patients using total sampling technique. The data obtained was processed statistically using the chi-square formula. Based on the results of the analysis, it was found that the majority had the characteristics of an average age of elderly 46-55 years (45.6%), gender was predominantly female (55.9%), high school respondent education (36.8%), housewife respondent's occupation (29.4%), glucose control uncontrolled blood pressure (61.8%), unhealthy diet (76.5%), low physical activity pattern (58.8%). The results of the study explain that there is a significant relationship between diet and activity patterns and blood sugar control with p-values ​​= 0.001 and 0.029 (p-value <0.05), respectively. It is recommended that people with type 2 diabetes mellitus be given education regarding what factors can trigger an increase in blood sugar levels.